Water Traffic Accidents Resulting in Death: Resolution Through Dayak Customary Law: - - Kristian Kristian; Ali, Nuraliah (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to examine the resolution mechanisms for water traffic accidents causing death through Dayak customary law in Central Kalimantan, as well as the challenges faced in implementing this customary law. The research used a socio-legal methodology, reviewing applicable legal norms and the reality of their implementation in society. Data were collected from literature reviews, case notes, related reports, and interviews with directly involved parties. Data analysis was conducted descriptively to depict the dispute resolution process and its challenges. The findings indicate that resolutions of water accident cases resulting in death in the Dayak region are often settled through local customary institutions using fines and customary rituals. The fines imposed vary depending on the level of fault determined and can amount to millions of Rupiah, adjusted according to the demands of the victim's heirs and the perpetrator's ability. However, challenges in applying this customary law include the limited ability of the Mantir Adat to determine suspects and resolve discrepancies in statements between involved parties. A lack of explicit regulations also poses challenges, particularly concerning penalties for cases of death not explicitly regulated in the prevailing customary law. This research is significant as it provides insights into the role and challenges of customary law in dispute resolution in remote communities, promoting the need for adaptation and strengthening of customary law to be more responsive to community needs.